Clinical and epidemiological characteristics of bilateral retinoblastoma in children of the national hospital edgardo rebagliati martins (hnerm), institute of neoplastic diseases and clinic oncosalud-auna, Lima-Peru 1999-2016 - Paredes Guerra, Gloria (2018)
ABSTRACT Objective: To describe the main epidemiological factors, methods of diagnosis and treatment of retinoblastoma in children of the Edgardo Rebagliati Martins National Hospital. Methods: A retrospective and descriptive study, clinical histories were reviewed, 25 patients with bilateral retinoblastoma were obtained. Descriptive statistics were used for the presentation and analysis of the results. Results: Predominance in preschoolers and males, leucocoria more frequent sign. Conclusion: In addition to what was mentioned in the results, it is more common diagnosis in advanced stages, most received systemic chemotherapy, more than 50% also focal therapy and 44% preserved unilateral vision. Key words: Retinoblastoma; Epidemiological factors; Diagnostic methods; Treatment. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1591